Depression and resilience mediate the relationship between traumatic life events and ill physical health: results from a population study. Issue 9 (21st October 2017) - Karatzias, Thanos; Jowett, Sally; Yan, Elsie; Raeside, Robert; Howard, Ruth
Abstract: We set out to investigate the mediating roles of depression, resilience, smoking, and alcohol use, in the relationship between potentially traumatic life events and objective and subjective, physical and mental health in a single study. A face-to-face, population-based survey was conducted in Hong Kong ( N  = 1147). Information on health conditions and traumatic life events was obtained, and participants completed measures of subjective physical and mental health, depression, and resilience. Smoking and drinking were not significant mediators of the relationship between life events and both objective and subjective health. Depressive symptomatology was found to mediate the relationship between life threatening illness and subjective physical health, the relationship between abuse (physical and sexual) and subjective mental health, and the relationship between the death of a parent/partner and subjective mental health. Resilience was found to mediate the relationships between multiple traumatic life events and subjective physical and mental health. Our results indicate that psychological factors rather than biological are important mediators of the relationship between life events exposure and health. Our findings provide evidence that depressive symptomatology has a mediating role only in the case of specific potentially traumatic life events and that resilience is only a critical factor in the face of exposure to multiple traumatic events, rather than single events. Our results also indicate that behavioural factors, such as smoking and drinking, are not significant mediators of the relationship between life events and health.